Longitudinal study of socio-emotional cognitive processing in individuals with anorexia nervosa and the impact of autistic characteristics on neural processing - Daniel Halls; Daniel Halls; Jenni Leppanen; Steve Williams; Kate Tchanturia; Kate Tchanturia; Kate Tchanturia (Frontiers in Psychology)
BackgroundDifficulties in socio-emotional cognitive processing are a key feature in individuals with anorexia nervosa (AN); however, the underlying neural processing, particularly longitudinal, is poorly understood. Compounding difficulties is the presence of overrepresented autistic characteristics, and it is unclear how these impact socio-emotional cognitive neural processing in individuals with AN.MethodA total of 92 participants, including 65 individuals with AN and 27 controls, took part in a longitudinal assessment at two time points, approximately 2 years apart, by undertaking socio-emotional cognitive tasks while undergoing functional magnetic resonance imaging (fMRI). A multivariate approach was used to predict autistic characteristics from generated maps from the AN group.ResultsA group-by-time interaction effect was demonstrated in several brain regions in response to tasks, with the regions with the strongest evidence being the right frontal operculum/pole. The multivariate approach revealed a wide distribution of brain regions contributing to autistic characteristics.ConclusionNeural changes over time in the right frontal operculum/pole potentially represent a compensatory mechanism for cognitive difficulties. Autistic characteristics in individuals with AN are instantiated and impact a wide distribution of neural regions, particularly during socio-emotional cognitive processing.